Analisis Faktor Yang Mempengaruhi Penggunaan E-Wallet Pendekatan Model UTAUT2 pada Generasi Z, di Wilayah DKI Jakarta - Vebriani Vebriani; Budi Prijanto (Bisnis-Net, 2026)
This study aims to analyze the factors influencing the intention and behavior of e-wallet usage among Generation Z in DKI Jakarta using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model. The rapid development of digital payment systems in Indonesia, especially OVO, GoPay, and DANA, has changed transaction behavior among young consumers. Generation Z is known as a digital native generation with high technology adoption, making it important to understand the determinants of their e-wallet usage behavior. This research uses a quantitative approach with a survey method involving respondents from Generation Z in DKI Jakarta who actively use e-wallet applications. Data were analyzed using Partial Least Square – Structural Equation Modeling (PLS-SEM). The results show that Hedonic Motivation, Price Value, and Habit have the strongest influence on Behavioral Intention, while Behavioral Intention and Facilitating Conditions significantly influence Use Behavior. Effort Expectancy is found to be insignificant due to the high digital literacy of Generation Z. These findings indicate that promotional value, user experience, and usage habits play a crucial role in encouraging sustained e-wallet usage among Generation Z.